1996
DOI: 10.1103/physrevc.54.1710
|View full text |Cite
|
Sign up to set email alerts
|

Isospin dependence of intermediate mass fragment production in heavy-ion collisions atE/A=55 MeV

Abstract: The production of intermediate mass fragments ͑IMF's͒ from the four reactions 55A MeV 124,136 Xe ϩ 112,124 Sn is studied with an experimental apparatus which is highly efficient for the detection of both charged particles and neutrons. The IMF's are more localized in the midvelocity region than are the light charged particles, and the detected multiplicity of IMF's depends linearly on the charge lost from the projectile and increases with the neutron excess of the system. Remnants of the projectile, with very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
87
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 24 publications
11
87
1
Order By: Relevance
“…The potential mechanisms of mid-rapidity emissions, as e.g. neck formation, and the isospin effects associated with it [39,40] are closely connected to several dynamical and statistical aspects of hot fragmentation, among them the isotopic separation expected in the liquid-gas coexistence zone [41][42][43]. These topics are the subjects of other plenary talks at this conference.…”
Section: Useful Reactionsmentioning
confidence: 99%
“…The potential mechanisms of mid-rapidity emissions, as e.g. neck formation, and the isospin effects associated with it [39,40] are closely connected to several dynamical and statistical aspects of hot fragmentation, among them the isotopic separation expected in the liquid-gas coexistence zone [41][42][43]. These topics are the subjects of other plenary talks at this conference.…”
Section: Useful Reactionsmentioning
confidence: 99%
“…An enhanced production of neutron rich H and He isotopes from the neck region has been seen experimentally in mid-peripheral collisions [8,9], while a favored emission of more symmetric heavy clusters in the mid-rapidity region has also been shown [10]. Quite neutron deficient residues have also been seen in intermediate energy reactions [11,12].…”
mentioning
confidence: 91%
“…In particular, the formation of a neck-like structure in peripheral heavy ion reactions and the impact on the fragmentation mechanism and production of light charged particles has been discussed for a couple of years [7][8][9][10][11][12][13][14][15][16][17][18][19]. It has been suggested that this neck instability can be important for the fast decomposition of matter and is probably neutron rich [20].…”
Section: Introductionmentioning
confidence: 99%